1925 Vol. XXV, No. 03, March 1925, Bulletin of the State Teachers College, Kirksville, Missouri, Announcements for the Summer Term, 1925 - Northeast Missouri State Teachers College (publisher not identified, 1925)
This is a digital copy of the summer bulletin of classes, courses of study, and lists of faculty and students for the academic year 1925-26, and announcements for the upcoming year.